The Effect of Return on Assets Ratio, Debt to Equity Ratio and Sales Growth on Tax Avoidance - Yanti (Jurnal Manajemen Bisnis, 2024)
This study aims to determine the role of Return On Assets Ratio (ROA), Debt To Equity Ratio (DER), and Sales Growth on Tax Avoidance, with a research focus on the Energy sector listed on the Indonesia Stock Exchange for the 2020-2022 period. A sample of 45 companies was used, taken using the purposive sampling technique. The data analysis technique used is quantitative analysis. This analysis shows that ROA and DER have a significant effect on Tax Avoidance, while sales growth has no effect. The data management procedure was carried out with the help of IBM SPSS 26.